Prevalence of depression in patients with type 2 diabetes attending an outpatient clinic in India. Issue 1068 (4th August 2014) - Siddiqui, Samreen; Jha, Sujeet; Waghdhare, Swati; Agarwal, Nidhi Bharal; Singh, Kalpana
Abstract: Background: Clinical studies have suggested that depression is common among patients with type 2 diabetes (T2D). Depression is an important factor which affects the management and complications of diabetes. However, the available data regarding its prevalence in India are limited. Objectives: To estimate the prevalence of depression in patients in India with T2D and to compare it with a non-diabetic group; and to determine the association of depression with glycaemic control and complications of diabetes in patients with T2D. Methods: This case–control study was carried out over 5 months from May to September 2012 at a tertiary care hospital in India. Cases were patients with T2D and controls were individuals without diabetes. Depression was assessed using the Patient Health Questionnaire (PHQ)-9. The sociodemographic profile, duration of diabetes, presence of complications and other medical variables were also analysed. Results: 260 subjects of Indian origin (162 men and 98 women; 130 with known T2D and 130 controls without T2D) were evaluated. The prevalence of depression in subjects with T2D was almost twice that in control subjects (46/130 (35.38%) vs 26/130 (20%); p=0.006). A statistically significant difference was found in the fasting blood glucose levels of subjects with depression and those without depression among the patients with T2D (145.70±53.92 vs 130.61±42.39; p=0.022), but depression was not found to be associated with any of the diabetic complications and glycaemic control. Conclusions: Our findings demonstrate that there is a higher prevalence of depression in Indian patients with T2D, which is almost twice that in those without T2D. Since patients with T2D are at higher risk of developing depression, assessment of depression should be performed as part of the routine practice in India. Trial registration number: CTRI/2012/06/002747.